Back Cover: Nitrogen‐Doped Carbon Embedded MoS2 Microspheres as Advanced Anodes for Lithium‐ and Sodium‐Ion Batteries (Chem. Eur. J. 33/2016). Issue 33 (21st June 2016) - Xie, Dong; Xia, Xinhui; Wang, Yadong; Wang, Donghuang; Zhong, Yu; Tang, Wangjia; Wang, Xiuli; Tu, Jiangping
Abstract : A facile polyurethane‐assisted hydrothermal method is reported for the synthesis of N‐C@MoS2 micropsheres. A uniform N‐doped carbon conductive and protective layer was realized on MoS2 flakes to form the N‐C@MoS2 microsphere. Owing to its unique structural features, the N‐C@MoS2 microspheres exhibit greatly enhanced lithium‐ and sodium‐storage performances including a high specific capacity, high rate capability, and excellent capacity retention. More information can be found in the Full Paper by J. Tu et al. onpage 11617 .